Embedding ESG into Strategic Management: Redesigning Corporate Strategy for Sustainable Competitiveness - Noch, Muhammad Yamin (Omnia Tempus, 2025)
This study investigates how Environmental, Social, and Governance (ESG) principles are embedded into strategic management and how such integration reshapes corporate strategy to achieve sustainable competitiveness. Positioned within a qualitative literature-based research design, the study synthesizes theoretical frameworks, empirical findings, and contemporary regulatory developments to construct a comprehensive understanding of ESG-driven strategic transformation. Using an integrative review method, the analysis draws on multidisciplinary scholarship to interpret patterns across environmental stewardship, social responsibility, and governance accountability as they relate to long-term value creation. The findings reveal that embedding ESG into strategic management enhances innovation capacity, strengthens stakeholder trust, and improves organizational resilience by aligning corporate objectives with broader sustainability imperatives. The review demonstrates that firms adopting ESG-oriented strategies outperform traditional competitors in areas such as risk mitigation, operational efficiency, and market reputation. The study further identifies persistent barriers, including inconsistent ESG metrics, risks of symbolic adoption, and institutional differences across global markets, which complicate uniform integration. Overall, the research contributes theoretically by reframing ESG as a core strategic capability rather than a compliance mechanism, and it offers managerial insights emphasizing the necessity of leadership commitment, transparent governance structures, and sustainability-oriented organizational cultures. These findings underscore ESG’s emerging role as a foundational determinant of competitive advantage in an increasingly sustainability-centered global economy.